TA’TSIIRU WASAAILI AT-TA’LIIMI POWERPOINT ‘ALAA NATAAIJI TA’LIIMI AL-LUGHAH AL-ARABIYAH - Nur Maya Badriyatul Jamroh; Dina Islamiana (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2020)
This study aims to determine how to implement the "Power Point" media and find out from these media the learning outcomes of Arabic in grade 1 SMA Al-Amiriyah Blokagung Banyuwangi. This research is directed at two main issues: 1) the use of PowerPoint as a learning medium for students, and 2) the level of impact and outcome of the "Power Point" media to determine student learning outcomes in Arabic. Researchers used quantitative research methods in this type of experimental research. The aim is to determine the effect of treatment on the experimental group and the control group. The population in this study were all grade I students of SMA MA Al-Amiriyah Blokagung Banyuwangi, with a total sample of 26 students. After analyzing the collected data, it was found that the influence of the "Power Point" media on the learning outcomes of Arabic class 1 MA Al-Amiriyah Blokagung Banyuwangi was 69.2%.